Profile of Sharon Y. Strauss - Jennifer Viegas (Proceedings of the National Academy of Sciences, 2025)
Evolutionary ecologist Sharon Y. Strauss, an early proponent of unifying the fields of ecology and evolution, helped advance both disciplines. Now a distinguished emeritus professor at the University of California, Davis, Strauss remains active in research. One major focus of her work is using phylogenetic evolutionary history to understand current ecology, an approach applied to research reported in her Inaugural Article. Strauss et al. determined that certain plant species may be less adaptable than expected to climate change. The finding holds widespread implications for conservation and management.